2000
DOI: 10.1046/j.1432-1327.2000.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual metabolic pathway of 25‐hydroxyvitamin D3 catalyzed by human CYP24

Abstract: Human 25-hydroxyvitamin D 3 (25(OH)D 3 ) 24-hydroxylase (CYP24) cDNA was expressed in Escherichia coli, and its enzymatic and spectral properties were revealed. The reconstituted system containing the membrane fraction prepared from recombinant E. coli cells, adrenodoxin and adrenodoxin reductase was examined for the metabolism of 25(OH)D 3 , 1a,25(OH) 2 D 3 and their related compounds. Human CYP24 demonstrated a remarkable metabolism consisting of both C-23 and C-24 hydroxylation pathways towards both 25(OH)D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
161
3
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(173 citation statements)
references
References 26 publications
6
161
3
3
Order By: Relevance
“…25[OH]D and 1, 25[OH]D can also be converted into less active moieties by the 24-hydoxylase, cytochrome P450, family 24, subfamily A, polypeptide 1 (CYP24A1). The expression of CYP24A1 is induced by 1, 25[OH] 2 D itself, providing a robust mechanism for negative feedback [7]. Therefore, the relative expression of these hydroxylases can serve to tightly regulate 1, 25[OH]D levels and activity during an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…25[OH]D and 1, 25[OH]D can also be converted into less active moieties by the 24-hydoxylase, cytochrome P450, family 24, subfamily A, polypeptide 1 (CYP24A1). The expression of CYP24A1 is induced by 1, 25[OH] 2 D itself, providing a robust mechanism for negative feedback [7]. Therefore, the relative expression of these hydroxylases can serve to tightly regulate 1, 25[OH]D levels and activity during an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of CYP24A1 structure and function is complicated by observations that the enzyme displays both C 23 -and C 24 -hydroxylase activity that depends on which side-chain carbon (C 23 or C 24 ) is hydroxylated first. Several studies have demonstrated that speciesspecific CYP24A1 isoforms express different levels of C 23 -and C 24 -hydroxylase activities that result in side-chain lactone formation (C23 pathway) or side-chain cleavage and oxidation to a carboxylic acid (C24 pathway) [18,19] Human CYP24A1 possesses both C 23 -and C 24 -activity, while the rat form seems to catalyze the C 24 pathway exclusively. Although the structural basis of this altered specificity remains elusive, Hanamoto et al have recently demonstrated that the C 23 -hydroxylase activity of rat CYP24A1 could be bolstered by humanizing single residues (T416M, I500T) within the enzyme's putative active site [20] ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations affecting CYP24A1 function correlate with incidents of idiopathic infantile hypercalcemia or hypercalciuria or elevated serum 1,25(OH) 2 D3 in adults (11)(12)(13)(14). In humans, CYP24A1 mediates hydroxylation of the vitamin D side chain at either carbon-23 (C23) or carbon-24 (C24), then mediates all subsequent steps in each pathway to produce either the metabolite 1,25(OH) 2 D3-26,23-lactone or calcitroic acid from the C23 or C24 pathways, respectively (15)(16)(17). While calcitroic acid is excreted in urine, 1,25(OH) 2 D3-26, 23-lactone has been demonstrated to modulate vitamin D signaling by binding the vitamin D receptor (18,19).…”
mentioning
confidence: 99%